2017
DOI: 10.3847/1538-4357/aa7261
|View full text |Cite
|
Sign up to set email alerts
|

Detection of GeV Gamma-Rays from HESS J1534−571 and Multiwavelength Implications for the Origin of the Nonthermal Emission

Abstract: HESS J1534-571 is a very high energy gamma-ray source that was discovered by the H.E.S.S. observatory and reported as one of several new sources with a shell-like morphology at TeV energies, matching in size and location with the supernova remnant G323.7-1.0 discovered in radio observations by the Molonglo Galactic Plane Survey. Many known TeV shells also show X-ray emission, however, no X-ray counterpart has been seen for HESS J1534-571. The detection of a new GeV source using data from the Fermi satellite th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Independent of the MAXI J1535−571 discovery, the existence of the cavity (Figure 1) favours a core-collapse supernova explosion model for the SNR, like that required to create a BH. The cavity is also consistent with SNR distance estimates from radio brightness (12), X-ray absorption ( 14) and gamma-ray emission modeling (15). Given the strong case for a relation between the SNR and BH, we used the SNR shock evolution modelling age estimate of 8-24 kyr (12) as a guide to model the history of this unique association.…”
supporting
confidence: 53%
“…Independent of the MAXI J1535−571 discovery, the existence of the cavity (Figure 1) favours a core-collapse supernova explosion model for the SNR, like that required to create a BH. The cavity is also consistent with SNR distance estimates from radio brightness (12), X-ray absorption ( 14) and gamma-ray emission modeling (15). Given the strong case for a relation between the SNR and BH, we used the SNR shock evolution modelling age estimate of 8-24 kyr (12) as a guide to model the history of this unique association.…”
supporting
confidence: 53%
“…Each CCD chip is placed on the focal plane of the X-Ray Telescope (XRT; Serlemitsos et al 2007 (Puehlhofer et al 2015). The cross point shows the brightness peak position of the GeV gamma-ray emission (Araya 2017).…”
Section: Observation and Data Reductionmentioning
confidence: 99%
“…results on HESS J1534−571, Araya (2017) has recently shown that a disk-like GeV counterpart to HESS J1534−571 can be extracted from Fermi-LAT data as well. The GeV source position and size are in good morphological agreement with G323.7−1.0 and HESS J1534−571.…”
Section: Gev Emission With Fermi-latmentioning
confidence: 94%